What predicts quality of life after subthalamic deep brain stimulation in Parkinson's disease? A systematic review. (24th January 2020) - Geraedts, V. J.; Feleus, S.; Marinus, J.; van Hilten, J. J.; Contarino, M. F.
Abstract : Background and purpose: Subthalamic deep brain stimulation (STN DBS) is an effective therapy against medication‐refractory motor complications in patients with Parkinson's disease. However, it remains difficult to predict which baseline patient characteristics are associated with quality of life (QoL) after surgery. The objective was to identify preoperative factors associated with QoL after STN DBS by systematically reviewing publications of sufficient methodological quality. Methods: Main databases were systematically searched up to March 2019 to identify studies that investigated factors associated with QoL after STN DBS in patients with idiopathic Parkinson's disease. Results: In all, 869 studies were identified, of which 18 fulfilled the inclusion criteria. Higher QoL after DBS appears to be associated with a large preoperative difference between ON and OFF motor function in some studies, although there was no clear association of severity of motor function or motor complications with postoperative QoL. Lower severity of dyskinesias was associated with greater postoperative QoL improvement but has been insufficiently studied. Higher baseline QoL was suggestive of higher postoperative QoL. Four studies suggested that older age at surgery is associated with a lower improvement, although six other studies reported no association. No or limited evidence was found for cognitive impairment or psychiatric dysfunction. Conclusion: Various relative contraindications for STN DBS such as cognitive impairment and psychiatric dysfunction appear to be unrelated to postoperative QoL. However, the lack of clear correlations with disease‐related variables suggests that QoL may be individually influenced by other factors, indicating that an ideal preoperative patient profile with regard to QoL improvement cannot be readily provided.